Effect of justice on employee performance in the banking sector of Pakistan - Amna Niazi; Hamid Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The main goal of this study was to examine the impact of the three dimensions of justice on organizational performance when trust mediates the relationship. The industry chosen for this study was the banking industry of Pakistan. The data were collected from a developing country to see how results differ when compared with already conducted studies on justice from a developed country. The present study also takes into consideration the three dimensions of justice rather than considering justice to be a one-dimensional or two-dimensional construct. A total of 300 respondents who were employees of banks participated in the study. A self-administered questionnaire was used to collect data. The findings of the study suggested that procedural and interactional justice had strong, positive and significant relationship with organizational trust but distributional justice had a weak but positive relationship with organizational trust. It was also empirically proved that organizational trust plays a vital role in determining organizational performance.
Keywords: 330; distributive justice; procedural justice; interactional justice; trust; employee performance; banking industry